Agricultural Scientists’ Perceptions of Working with Reporters - Taylor K Ruth; Laura E Young; Joy N Rumble; Lisa K Lundy (Journal of Applied Communications, 2021)
Mass media is the main source of scientific information for most Americans, but inaccuracy of reporting has threatened the public’s understanding of science. Perceived media bias and fake news has also made the public skeptical of the media, and scientists’ perceptions are no different. Because scientists are the most trusted source for scientific information in America, it is important they remain willing to work with the media. This study used the Theory of Planned Behavior (TPB) to explore scientists’ perceptions of working with reporters, including their attitude, subjective norms, behavioral control, and intent to engage with the media in the future. In-depth interviews were conducted with 13 tenure-track faculty at the University of Florida’s Institute of Food and Agricultural Sciences (UF/IFAS) in spring 2018. These participants represented low, moderate, and high communicators. The findings from this study indicated mostly negative attitudes toward reporters due to skepticism in their ability to accurately report science. Behavioral control was also limited due to time and ability constraints, but participants recommended trainings as ways to increase behavioral control. Subjective norms were somewhat mixed, with some positive norms from mentors but perceived negative norms from the public. Despite negative attitudes toward reporters, intent to engage with the media was mixed. However, subjective norms and behavioral control were often discussed as reasons to not engage with reporters. The findings from this study offered recommendations for both practice and research to help foster positive relationships between scientists and reporters.
Keywords: scientists; media; reporters; science literacy; theory of planned behavior